(untitled) (Bioresearch Communications, 2025)
Human metapneumovirus (HMPV) and severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) are major respiratory pathogens. This study investigates whether prior SARS-CoV-2 infection or COVID-19 vaccination provides cross-protection against HMPV. Nucleotide sequences of HMPV, SARS-CoV-2, and mRNA vaccines (Moderna and Pfizer-BioNTech) were retrieved from the NCBI database. Multiple sequence alignment, BLAST analysis, sequence dot plot and phylogenetic tree construction were performed to assess genetic and structural similarities. Results revealed no significant sequence homology between SARS-CoV-2 genome, structural proteins, mRNA vaccine sequences, and HMPV. HMPV does not share any common linear peptide epitope with SARS-CoV-2. This indicates a complete lack of cross-immunity. Phylogenetic analysis confirmed the distinct evolutionary divergence between these viruses. The resurgence of HMPV infections following the relaxation of COVID-19 restrictions further underscores the need for independent surveillance and vaccine development. These findings highlight the necessity for targeted immunization strategies against HMPV to mitigate future outbreaks. Bioresearch Commu. 11(2): 1778-1786, 2025 (July)